2013
DOI: 10.1038/npp.2013.28
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic κ-Opioid Receptor Modulates the Orexigenic Effect of Ghrelin

Abstract: The opioid system is well recognized as an important regulator of appetite and energy balance. We now hypothesized that the hypothalamic opioid system might modulate the orexigenic effect of ghrelin. Using pharmacological and gene silencing approaches, we demonstrate that ghrelin utilizes a hypothalamic k-opioid receptor (KOR) pathway to increase food intake in rats. Pharmacological blockade of KOR decreases the acute orexigenic effect of ghrelin. Inhibition of KOR expression in the hypothalamic arcuate nucleu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 47 publications
1
40
0
Order By: Relevance
“…Interestingly, the converse was true for the VTA delivery of a mu-preferring opioid receptor antagonist, which suppressed the effects of VTA ghrelin on food motivation but not food intake (111). Kappa opioid receptor pathways at the hypothalamic level also appear to be a component of the ghrelin sensitive circuitry that is important for feeding control (112). Collectively, these studies outline the divergence of behaviours (food motivation and food intake), involving overlapping but also distinct neurochemical pathways.…”
Section: Neuronal Circuits Mediating the Effects Of Ghrelin On Food Rmentioning
confidence: 95%
“…Interestingly, the converse was true for the VTA delivery of a mu-preferring opioid receptor antagonist, which suppressed the effects of VTA ghrelin on food motivation but not food intake (111). Kappa opioid receptor pathways at the hypothalamic level also appear to be a component of the ghrelin sensitive circuitry that is important for feeding control (112). Collectively, these studies outline the divergence of behaviours (food motivation and food intake), involving overlapping but also distinct neurochemical pathways.…”
Section: Neuronal Circuits Mediating the Effects Of Ghrelin On Food Rmentioning
confidence: 95%
“…Adult (8-10 weeks old) wild type (WT) C57BL6 mice, mutant mice (Oprk1 -/-) that lack functional k-OR subtype 1 (B6.129S2-Oprk1 tm1kff /J, The Jackson Laboratory) (Imbernon et al, 2016;Romero-Picó et al, 2013), were maintained on an ad libitum chow diet in Specific Pathogen Free (SPF) conditions and housed with a 12:12-h light-dark cycle. For surgery, mice were anesthetized by an intraperitoneal injection of 138 mg ketamine/Kg BW + 7 mg xylacine/Kg BW.…”
Section: Animal Procedures and Chemicalsmentioning
confidence: 99%
“…However, there is a general lack of information regarding the interaction with other hypothalamic systems. Opioid receptors are widely expressed within the hypothalamus (Mansour et al, 1994), and we have previously demonstrated that the k-OR system in the ARC is able to modulate the orexigenic effect of ghrelin (Romero-Picó et al, 2013). A potential interaction among MCH and the opioid system to regulate food intake and food addiction was postulated previously (Lopez et al, 2011), but the mechanistic aspects and the specific brain areas where this interaction occurs remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Central NPY and opioid system have been identified as well as necessary mediators of reward effects of ghrelin in the mesolimbic VTA (Skibicka, Shirazi, Hansson, & Dickson, ). Likewise, the hypothalamic proDyn/KappaOR pathway (Romero‐Pico et al, ) and lateral septum (Terrill, Wall, Medina, Maske, & Williams, ) also appear to be components of the ghrelin circuitry of feeding motivation. Recently, it has also been demonstrated that the ghrelin pathway could be implicated in learned feeding responses.…”
Section: Eating Beyond Metabolic Needs: the Nonhomeostatic Role Of Pementioning
confidence: 99%